Comparação de índices de vegetação para avaliação da ação de defensivos na cultura da mandioca - Lima, Luane Araújo (2025)
Cassava is a crop of great national and international importance, being widely used in human and animal food, in addition to serving as a raw material for several industries. Advances in technologies in agriculture, such as remote sensors and drones, allow for the precise analysis of essential crop variables, optimizing the use of inputs, increasing productivity, and promoting more efficient and sustainable management. Image phenotyping, using sensors in the visible spectrum (RGB) and near-infrared (IVP) using ARP to obtain the same, facilitates the image capture process, being an important low-cost and high-resolution plataform. In this way, the aim is to extract vegetative indeces in cassava crops and, subsequently study the pigments of the cultivars. For this, the DJI Mavic 3M ARP and the FieldImageR tool were used. Thus, vegetation indices were generated to verify the correlation of each one with the phenotypic characteristics of cassava. The results reinforce the relevance of integrated approaches that combine digital tools, visual assessments, and agronomic knowledge, aiming at the sustainable management of cassava and the optimization of the use of herbicides in the crop.